RNA Interference for Improving Disease Resistance in Plants and Its Relevance in This Clustered Regularly Interspaced Short Palindromic Repeats-Dominated Era in Terms of dsRNA-Based Biopesticides - Halder, Koushik; Chaudhuri, Abira; Abdin, Malik Z.; Majee, Manoj; Datta, Asis (Frontiers in Plant Science, 2022)
RNAi has been exploited by scientists worldwide to make a significant contribution in the arena of sustainable agriculture and integrated pest management. These strategies are of imperative need to guarantee food security for the teeming millions globally. The already established deleterious effects of chemical pesticides on human and livestock health have led researchers to exploit RNAi as a potential agri-biotechnology tool to solve the burning issue of agricultural wastage caused by pests and pathogens. On the other hand, CRISPR/Cas9 the latest genome-editing tool also has a notable potential in this domain of biotic stress resistance and a constant endeavor by various laboratories are in progress for making pathogen-resistant plants using this technique. Considerable outcry regarding the ill effects of genetically modified (GM) crops on the environment paved the way for the research of RNAi-induced double-stranded RNAs and their application to biotic stresses. Here, we mainly focus on the application of RNAi technology to improve disease resistance in plants and its relevance in today's CRISPR dominated world in terms of exogenous application of dsRNAs. We also focused on the ongoing research, public awareness and subsequent commercialization of dsRNA-based biocontrol products.